2009
DOI: 10.1007/s12539-009-0059-0
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic detection of HIV DNA in the blood of AIDS patients treated by antiretroviral therapy

Abstract: Electromagnetic signals of low frequency have been shown to be durably produced in aqueous dilutions of the Human Imunodeficiency Virus DNA. In vivo, HIV DNA signals are detected only in patients previously treated by antiretroviral therapy and having no detectable viral RNA copies in their blood. We suggest that the treatment of AIDS patients pushes the virus towards a new mode of replication implying only DNA, thus forming a reservoir insensitive to retroviral inhibitors. Implications for new approaches aime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 5 publications
5
36
0
Order By: Relevance
“…Our standpoint is consistent with previous experimental work [3][4][5][6] that has shown that some DNAs in water dilutions emit electromagnetic waves of low frequency (from hundreds to 3 kHz) which could be triggered, as in a resonance phenomenon, by an outside excitation, such as the Schumann waves [19]. Experimental peaks of Schumann waves are at 7.83, 14.3, 20.8, 27.3, and 33.8 Hz; the peak near 7 Hz is the one found to be minimally active in the case discussed here (for further details see [3][4][5][6]).…”
Section: The Taq-dna Interaction and Open Questionssupporting
confidence: 93%
See 4 more Smart Citations
“…Our standpoint is consistent with previous experimental work [3][4][5][6] that has shown that some DNAs in water dilutions emit electromagnetic waves of low frequency (from hundreds to 3 kHz) which could be triggered, as in a resonance phenomenon, by an outside excitation, such as the Schumann waves [19]. Experimental peaks of Schumann waves are at 7.83, 14.3, 20.8, 27.3, and 33.8 Hz; the peak near 7 Hz is the one found to be minimally active in the case discussed here (for further details see [3][4][5][6]).…”
Section: The Taq-dna Interaction and Open Questionssupporting
confidence: 93%
“…Experimental peaks of Schumann waves are at 7.83, 14.3, 20.8, 27.3, and 33.8 Hz; the peak near 7 Hz is the one found to be minimally active in the case discussed here (for further details see [3][4][5][6]). The electromagnetic signals (EMS) can be amplified and recorded as a digital form.…”
Section: The Taq-dna Interaction and Open Questionsmentioning
confidence: 59%
See 3 more Smart Citations